The Influence Of Vocabulary and Grammar Masteryon The Students’ Writing Skill At Yogyakarta State University - Saptin Dwi Setyo Hastuti (Media Wisata, 2015)
This study aims to investigate the influence of (1) the students’ vocabulary mastery on their writing skills, (2) the students’ grammar mastery on their writing skill and(3) the students’ vocabulary and grammar mastery on their writing skills at Yogyakarta State University. This research was an ex-post-facto. The population comprised the third-semester students of the Pendidikan Bahasa Inggris (PBI) study program at the Languages and Arts Faculty, Yogyakarta State University in the academic year 2013/2014. Therefore, this study showed that (1) vocabulary mastery positively influenced the students’ writing skills, (2) grammar mastery positively influenced the students’ writing skills, and (3) vocabulary and grammar mastery positively influenced the students’ writing skills.